Pengaruh ZIS, Dana Bagi Hasil dan Dana Alokasi Umum Terhadap Pertumbuhan Ekonomi di Indonesia - Atia Anggraini; Tri Inda Fadhila Rahma; Khairina Tambunan (Universitas Islam Negeri Sumatera Utara Medan, 2022)
This study was conducted to determine how much influence Zakat, Infaq and Sadaqah, Revenue Sharing Funds and General Allocation Funds have on Economic Growth in Indonesia. The data used in this study are secondary data obtained from the official website of the National Amil Zakat Agency and the Central Statistics Agency. This research is a quantitative research with multiple linear regression analysis model. The dependent variable used is Economic Growth. While the independent variables used are Zakat, Infaq and Sadaqah, Profit Sharing Funds and General Allocation Funds. This study uses the help of Eviews 10 as an estimation tool. From the research, it is found that Zakat, Infaq and Shadaqah have a positive but not significant effect on Economic Growth in Indonesia, the Profit Sharing variable has a negative and significant effect on Economic Growth in Indonesia and the General Allocation Fund variable has a positive and significant effect on Economic Growth in Indonesia. The results also show a coefficient of determination of 0.905260 which indicates that the independent variables provide an explanation of the dependent variable by 90%. The other 10% is explained by other variables outside the model.